Expert consensus on endodontic therapy for patients with systemic conditions - Xin Xu; Xin Zheng; Fei Lin; Qing Yu; Benxiang Hou; Zhi Chen; Xi Wei; Lihong Qiu; Chen Wenxia; Jiyao Li; Lili Chen; Zuomin Wang; et al. (Nature Publishing Group, 2024)
Abstract The overall health condition of patients significantly affects the diagnosis, treatment, and prognosis of endodontic diseases. A systemic consideration of the patient's overall health along with oral conditions holds the utmost importance in determining the necessity and feasibility of endodontic therapy, as well as selecting appropriate therapeutic approaches. This expert consensus is a collaborative effort by specialists from endodontics and clinical physicians across the nation based on the current clinical evidence, aiming to provide general guidance on clinical procedures, improve patient safety and enhance clinical outcomes of endodontic therapy in patients with compromised overall health.